2018
DOI: 10.1089/soro.2017.0097
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Soft Robotic Wrist for Underwater Manipulation

Abstract: This article presents the development of modular soft robotic wrist joint mechanisms for delicate and precise manipulation in the harsh deep-sea environment. The wrist consists of a rotary module and bending module, which can be combined with other actuators as part of a complete manipulator system. These mechanisms are part of a suite of soft robotic actuators being developed for deep-sea manipulation via submersibles and remotely operated vehicles, and are designed to be powered hydraulically with seawater. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 19 publications
0
64
0
Order By: Relevance
“…Previous studies have shown the promising features of soft robots for the deep sea application (Calisti et al, 2011;Cianchetti et al, 2015;Galloway et al, 2016;Licht et al, 2017;Kurumaya et al, 2018;Phillips et al, 2018;Teoh et al, 2018). In this paper, we demonstrate a soft manipulator system with dexterous motions, which aims for the shallow water seafood animal grasping (sea cucumbers, echini, etc.).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the promising features of soft robots for the deep sea application (Calisti et al, 2011;Cianchetti et al, 2015;Galloway et al, 2016;Licht et al, 2017;Kurumaya et al, 2018;Phillips et al, 2018;Teoh et al, 2018). In this paper, we demonstrate a soft manipulator system with dexterous motions, which aims for the shallow water seafood animal grasping (sea cucumbers, echini, etc.).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Recently, increasing studies on soft robotics have focused on the underwater applications. For example, robotic octopus arms achieved underwater locomotion (Calisti et al, 2011;Cianchetti et al, 2015); soft gripper has been used for biological sampling the coral reefs (Galloway et al, 2016); the origami gripper was applied to collecting delicate midwater organisms (Teoh et al, 2018); the jamming gripping was exploited in handling in deep sea (Licht et al, 2017); a soft glove was integrated to tele-operated control the soft wrist modules for biological underwater grasping (Kurumaya et al, 2018;Phillips et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] In particular, the inherent adaptation and waterproofing of soft actuators are ideal for grabbing delicate and flexible objects underwater, [16][17][18] inherited from cable-driven 19 and biomimetic approaches. [20][21][22][23] Fluidic elastomer actuators also work well in underwater applications, in terms of continuum structures, 24 hybrid structures, 25 and even modular structures, 26 tested in a high pressure environment equivalent to 2300 m depth. Three-dimensional printed soft robotic manipulators have also been proven highly successful in deep-sea operations, 27,28 tested for more than 2200 m depth, 29 offering much better compactness and inherent compliance than rigid manipulators for delicate underwater sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Soft modules are manufactured using soft materials, such as silica gel or rubber, which have characteristics of flexibility and continuous deformation. Therefore, many researchers have studied soft modular robots, including omnidirectional soft robots [13], rotary soft module and bending soft module [14], three types of pneumatically actuated soft modules (SoBL) [15], the soft modular robot with connecting part [16], elastomeric hollow cubes with magnetic connecting mechanisms [17], bidirectional bending modules [18], pneumatic actuators with four chambers [19], multi-spherical modular soft robots [20][21][22][23], bending-type fluidic elastomer actuators [24], modular soft robots with voice coil actuators [25], soft-bodied caterpillar-like modular robots [26], and vacuum-powered soft pneumatic actuator (V-SPA) modules [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have concentrated their attention on the structure of the soft module. Kurumaya presented the rotary soft module and bending soft module, which can be combined with other actuators as part of a complete manipulator system [14]. Lee designed three types of pneumatically actuated soft modules, which can connect with each other through a unified connecting part [15].…”
Section: Introductionmentioning
confidence: 99%